Etiology of Small Bowel Thickening on Computed Tomography - Lee Finkelstone; Ellen Wolf; Marjorie W Stein (Canadian Journal of Gastroenterology)
BACKGROUND: Abdominal pain is often evaluated using imaging, most often with computed tomography (CT). While CT is sensitive and specific for certain diagnoses, small bowel thickening is a nonspecific finding on CT with a broad differential diagnosis including infection, inflammation, ischemia and neoplasm.